The Effect of Exposure to Ultraviolet Rays of the Sun on Cataract Occurrence in Residents in Coastal Areas - I Gede Bramantya Surya Mahendra; Marie Yuni Andari (Science Midwifery, 2022)
A cataract is a condition in which the crystalline lens of the eye becomes cloudy. One of the risk factors that make a person more susceptible to developing cataracts is frequent exposure to the sun's ultraviolet (UV) rays. Exposure to the sun's ultraviolet B (UVB) rays can accelerate the development of cataracts. A person who suffers from cataracts will complain of visual disturbances, such as decreased vision, foggy and smoky vision, double vision, glare when seeing, impaired colour vision, difficulty seeing when the light is dim or at night, and seeing halos around light. . Management of cataract patients, namely surgical removal of the lens and replacing it with an intraocular lens (IOL). Prevention that can be done to reduce the risk of cataracts is to avoid sun exposure in the hours of the highest exposure intensity, wear sunglasses with UV filters, wear contact lenses with UV filters, and wear hats with wide edges.